2020
DOI: 10.1089/cap.2019.0041
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine for Pediatric Obsessive-Compulsive Disorder: A Small Pilot Study

Abstract: Background: Many children and adults with Obsessive-Compulsive Disorder (OCD) fail to respond to first-line pharmacological and behavioral treatments. Glutamate dysfunction may contribute to the development of OCD. N-acetylcysteine (NAC), a glutamate modulating drug, has shown to be a promising agent in adults with OCD. Methods: We conducted a double-blind, placebo-controlled clinical trial from July 2012 to January 2017. Children ages 8 to 17 years with OCD were assigned to receive NAC (up to 2700 mg/day) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…Although the effects of NAC on SSRI‐resistant OCD are ambiguous, the administration of NAC (1 g day −1 for a week followed by 2 g day −1 for 9 weeks) in combination with the SSRI citalopram significantly decreased OCD symptoms in 34 paediatric and adolescent outpatients (age: 10–21 years) with OCD in a 10‐week multicentre randomized double‐blind placebo‐controlled trial (Ghanizadeh et al, 2017). The same conclusion was obtained from a recent, small ( n = 11) double‐blind, placebo‐controlled clinical trial on the effects of NAC on paediatric patients with OCD (Li et al, 2020). NAC (up to 2.7 g day −1 for 12 weeks) administration in children (age: 8–17 years) who were also on stable psychiatric treatment (drug and therapy) evoked a significant reduction in OCD symptoms beginning at week 8.…”
Section: Nac In Psychiatric Disorders—clinical Studiessupporting
confidence: 75%
See 1 more Smart Citation
“…Although the effects of NAC on SSRI‐resistant OCD are ambiguous, the administration of NAC (1 g day −1 for a week followed by 2 g day −1 for 9 weeks) in combination with the SSRI citalopram significantly decreased OCD symptoms in 34 paediatric and adolescent outpatients (age: 10–21 years) with OCD in a 10‐week multicentre randomized double‐blind placebo‐controlled trial (Ghanizadeh et al, 2017). The same conclusion was obtained from a recent, small ( n = 11) double‐blind, placebo‐controlled clinical trial on the effects of NAC on paediatric patients with OCD (Li et al, 2020). NAC (up to 2.7 g day −1 for 12 weeks) administration in children (age: 8–17 years) who were also on stable psychiatric treatment (drug and therapy) evoked a significant reduction in OCD symptoms beginning at week 8.…”
Section: Nac In Psychiatric Disorders—clinical Studiessupporting
confidence: 75%
“…(n = 11) double-blind, placebo-controlled clinical trial on the effects of NAC on paediatric patients with OCD (Li et al, 2020). NAC (up to 2.7 g day À1 for 12 weeks) administration in children (age: 8-17 years) who were also on stable psychiatric treatment (drug and therapy) evoked a significant reduction in OCD symptoms beginning at week 8.…”
Section: Controlledmentioning
confidence: 99%
“…[46][47][48][49][50] Of note, a recent small open trial on pediatric OCD patients showed some initial positive effects of NAC on OCD symptoms. 51 On the other hand, L-carnosine has been less investigated for OCD, but the only available controlled trial (1 g of L-carnosine as add on to fluvoxamine) showed good results. 55,56 Lamotrigine and Topiramate Lamotrigine and topiramate are two inhibitors of the glutamate AMPA (alpha-amino-3-hydroxy-5-methyl-4-isoxazole-propionate) receptors.…”
Section: N-acetylcysteine (Nac) and L-carnosinementioning
confidence: 99%
“…N-acetylcysteine (NAC) is a synthetic derivative of the endogenous amino acid L-cysteine that is able to modulate glutamatergic neurotransmission and the excitatory/inhibitory ratio (26,27). Furthermore, the anti-oxidant properties of NAC are relevant to the pathogenesis of several neuropsychiatric disorders (28)(29)(30)(31)(32)(33). Indeed, NAC is an essential substrate for the enzyme γ-glutamyl-cisteine synthetase (GCL) in the synthesis of glutathione (GSH), the main antioxidant in tissues (34).…”
Section: Introductionmentioning
confidence: 99%